Love Everlasting - Peterson, Tracie (Minneapolis, Minnesota : Bethany House, a division of Baker Publishing Group, 2015)
"After the great fire that destroyed much of Seattle in 1889, Abrianna Cunningham recognizes that her longtime friendship with Wade Ackerman is changing, but she finds herself overwhelmed by her conflicting feelings and the pursuit of another relentless suitor"--
Keywords: Man-woman relationships -- Fiction; Romance fiction; Historical fiction